Changes in Running Performance After Four Weeks of Interval Hypoxic Training in Australian Footballers: A Single-Blind Placebo-Controlled Study. Issue 11 (November 2015) - McLean, Blake D.; Tofari, Paul J.; Gore, Christopher J.; Kemp, Justin G.
Abstract : Abstract: McLean, BD, Tofari, PJ, Gore, CJ, and Kemp, JG. Changes in running performance after four weeks of interval hypoxic training in Australian footballers: A single-blind placebo-controlled study. J Strength Cond Res 29(11): 3206–3215, 2015—There is a paucity of data examining the impact of high-intensity interval hypoxic training (IHT) on intermittent running performance. This study assessed the effects of IHT on 17 amateur Australian Footballers, who completed 8 interval treadmill running sessions (IHT [FI O2 = 15.1%] or PLACEBO) over 4 weeks, in addition to normoxic football (2 per week) and resistance (2 per week) training sessions. To match relative training intensity, absolute IHT intensity reduced by 6% of normoxic vV[Combining Dot Above]O2 peak compared with PLACEBO. Before and after the intervention, performance was assessed by Yo-Yo intermittent recovery test level 2 (Yo-Yo IR2) and a self-paced team sport running protocol. Standardized effect size statistics were calculated using Cohen's d to compare between the interventions. Compared with PLACEBO, IHT subjects experienced (a) smaller improvements in Yo-Yo IR2 performance (Cohen's d = −0.42 [−0.82 to −0.02; 90% confidence interval]); (b) similar increases in high-intensity running distance during the team sport protocol ( d = 0.17 [−0.50 to 0.84]); and (c) greater improvements in total distance ( d = 0.72 [0.33–1.10]) and distance covered during low-intensity activity ( d = 0.59 [−0.07 to 1.11]) during the team sport protocol. The lower absolute training intensity of IHT may explain the smaller improvements in Yo-Yo IR2 performance in the hypoxic group. Conversely, the data from the self-paced protocol suggest that IHT may positively influence pacing strategies in team sport athletes. In conclusion, IHT alters pacing strategies in team sport athletes (i.e., increased distance covered during low-intensity activity). However, IHT leads to smaller improvements in externally paced high-intensity intermittent running performance (i.e., Yo-Yo IR2), which may be related to a reduced absolute training intensity during IHT sessions.